Peningkatan Masyarakat Cermat Menggunakan Obat di Desa Tatah Mesjid Handil Bakti - Fauzi, Muhammad; Ramadhani, Juwita; Hasniah, Hasniah; Susanto, Didi (Jurnal Pengabdian Kepada Masyarakat Kalam, 2024)
Antibiotics are drugs used to treat patients with bacterial infections. Antibiotics must be used rationally, accurately, and safely. Antibiotics are supposed to be obtained with a doctor's prescription. Public service activities by the UNISKA MAB Banjarmasin Pharmaceutical Faculty team were carried out in Tatah Mesjid Handil Bakti Village. The methods to do this are lectures, questions and health checks. The result is an understanding of helping people use medicines wisely as antibiotics for long-term health security